When nonstandard meets standard: Language and affective dynamics in accent-diverse group interactions - Merrisa Lin; Nairán Ramírez-Esparza; Alexandra Paxton (PLoS ONE, 2026)
Drawing on communication accommodation theory, this exploratory research examines how the arrival of a standard-accented newcomer influences nonstandard-accented participants’ linguistic patterns and positive affect during group interactions. While prior work often focuses on how newcomers adapt to groups, less is known about how a newcomer shifts existing group dynamics—especially in accent-diverse contexts. Across 49 WebEx group discussions involving 102 nonstandard-accented participants, a standard-accented confederate newcomer joined midway through each session. Study 1 examined changes in participants’ linguistic patterns, including linguistic style matching, speech mistakes, filler words, clout, and authenticity. Results showed that participants generally diverged from each other and converged toward the newcomer in linguistic style. They also made more speech mistakes, exhibited higher clout, and reduced authenticity, although they used fewer filler words—suggesting a disruption to existing interaction dynamics. Study 2 explored whether participants’ positive affect predicted perceived interaction quality after the newcomer’s arrival. Positive affect more strongly predicted perceived interaction quality than negative affect—suggesting that participants view the newcomer as more facilitative than disruptive. These findings highlight a complex dynamic of communication adaptation in accent-diverse interactions, where linguistic shifts are disrupted even as affect remains more positive. Implications for group integration and second-language training are discussed.